Class, migrants, and the European city: spatial impacts of structural changes in early twenty-first century Amsterdam. Issue 6 (2nd May 2016) - van Gent, Wouter; Musterd, Sako
ABSTRACT: Prevailing Anglo-Saxon theories on urban segregation based on class and 'migrant-status' have often been rejected for continental European cities, mainly because of different economic and labour market structures and higher levels of state interventions and welfare support in the latter type of cities. As urban economies in continental Europe are growing ever more global and welfare states are in continuous restructuring we seek to investigate whether a typical European socially balanced migrant city, the city (and metropolitan region) of Amsterdam, is developing into the direction of a more outspoken 'double dual' condition with populations getting more spatially segregated in terms of class and migrant status. This study looks at developments in terms of the spatial dynamics of the 'native' and immigrant population of different classes. We find that the region is undergoing a transformation, which for now reduces spatial concentrations and inequality. As the urban core is gentrifying and some suburban neighbourhoods are declining, the typical dichotomy of a poor-migrant central city versus affluent-native suburbs is vanishing. These developments point to a different type of social-migrant city, one with a patchwork of residential milieus along social and cultural lines. However, we challenge the sustainability of that patchwork over time.